TANGGUNG JAWAB NOTARIS TERHADAP SERTIFIKAT HAK ATAS TANAH YANG HILANG AKIBAT PENCURIAN DITINJAU DARI HUKUM PERDATA - Qumarudin, Jeffri; Sesung, Rusdianto (Fakultas Hukum Universitas Narotama, 2024)
A notary is an official who has the authority to make authentic deeds. The authentic deed itself functions as the most perfect piece of evidence in court, in the event of preservation of related rights and obligations. With the authority granted by law and the trust of the people served through legal traffic, it cannot be denied that in the process of transferring names, you will certainly receive a mandate from the applicant to keep the certificate of title to the land. In this research, the author analyzes the authority and responsibilities of Notaries in storing certificates of land rights lost due to theft. The type of research used is normative juridical or library research. The approach method is a statutory-regulatory approach, which means the approach is carried out by examining all laws and regulations related to the legal issue being handled. Basically, the notary himself does not have the authority to store land title certificates. This attitude is a form of neutral attitude that the notary has towards the parties to ensure legal certainty and protection. so that the notary indirectly assumes responsibility for storing land title certificates, including the obligation to safeguard the certificates, with the trust given by the parties. So that the Notary's form of responsibility must be carried out in accordance with the provisions of Article 1706 of the Civil Code (BW), which regulates that the Notary is also required to maintain and guard the certificate. The notary is obliged to compensate for damage or loss of land title certificates as reflected in Article 1694 of the Civil Code (BW). Thus, the notary's responsibility for land title certificates lost due to theft can be carried out in the form of compensation in the form of a replacement certificate. Keywords: Liability, theft, replacement certificate